Komodifikasi Anak dalam Variety Show Korea Selatan The Return of Superman (TROS) - Irani Yosef (Jurnal ILMU KOMUNIKASI, 2022)
This study aims to determine the practices of child commodification in a South Korean variety show: The Return of Superman (TROS). This study uses qualitative research methods through Van Dijk's critical discourse analysis (CDA). The results show that there was a commodification of children hidden behind the title of the program; this program is a product of popular culture with capitalist practices as a background: profit-oriented and market-regulated; and variety show interpreted more negatively because it has exploited the commodification practices and abuse of children's rights in the interest of the media.